Penanaman Moral dan Karakter Anak Usia Dini dari Nilai-Nilai Pancasila dengan Metode Nyata Belajar di Ranah PAUD - Leni Puspita Dewi; Budi Rachman (Indonesian Journal of Society Engagement, 2022)
The Indonesian nation has several rules in its government, regulations or national identity are contained in Pancasila. In Pancasila there are five precepts or five basics that contain national values. These values ??must be applied from early childhood. Moral values ??and character values ??in children can be formed from Pancasila values. The moral of early childhood is the conscience possessed by children to behave in accordance with the rules in society. Moral development is marked by the understanding and awareness of the individual to act in accordance with the rules that are required to be applied since the child reaches an early age. The character of the child is a description of the child's behavior that can be judged from the norms of the community environment. This study aims to analyze children's learning to improve the morality and character of children for the Indonesian nation in the future. Through a literature study research method approach, there are findings that children's moral and character cultivation of Pancasila values ??from this research can use various methods and media. Methods and media that can be used to teach children include playing methods, storytelling methods, demonstration methods, and many other methods.